2019
DOI: 10.1002/cbic.201900409
|View full text |Cite
|
Sign up to set email alerts
|

Cover Feature: Design of an Ultrafast G Protein Switch Based on a Mouse Melanopsin Variant (ChemBioChem 14/2019)

Abstract: The primary goal of optogeneticsi st he light-controlled noninvasive and specific manipulation of various cellular processes. Herein, we present ah ybrid strategy for targeted protein engineering combining computational techniques with electrophysiologicala nd UV/visible spectroscopic experiments.W ev alidated our concept for channelrhodopsin-2 and applied it to modify the less-well-studied vertebrate opsin melanopsin. Melanopsin is ap romising optogenetic tool that functions as a selectivem olecular light swi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…We further characterized the properties of light‐induced G i/o signaling via UVLamP in detail in vitro and found that its light‐induced activation and deactivation time constants with 1.15 s for activation and 4.95 s for deactivation (Figure A). These time constants are even faster than those of wild‐type mouse melanopsin (≈1.4 and ≈8.5 s, respectively) and comparable with the recently engineered Y211F mutant . We next investigated the minimal light pulse duration for activation and deactivation of GIRK channels using UVLamP.…”
Section: Figurementioning
confidence: 90%
See 3 more Smart Citations
“…We further characterized the properties of light‐induced G i/o signaling via UVLamP in detail in vitro and found that its light‐induced activation and deactivation time constants with 1.15 s for activation and 4.95 s for deactivation (Figure A). These time constants are even faster than those of wild‐type mouse melanopsin (≈1.4 and ≈8.5 s, respectively) and comparable with the recently engineered Y211F mutant . We next investigated the minimal light pulse duration for activation and deactivation of GIRK channels using UVLamP.…”
Section: Figurementioning
confidence: 90%
“…Recently, we characterized mouse and human homologues of melanopsin, another non‐visual opsin that can be found in intrinsically photosensitive retinal ganglion cells (ipRGCs) of the vertebrate retina and is involved in multiple physiological processes, for example, the circadian rhythm. We could show that melanopsin is a bistable/tristable opsin and a unique optogenetic tool that can be switched on/off with blue/green light pulses and can precisely control the G i/o and G q pathway in different expression systems like the mouse brain . Despite its advantageous characteristics, like high light sensitivity, bistable switching between sustained active and inactive states with short light pulses and strong expression in different systems, two drawbacks remained: First, melanopsin is activated/deactivated in the visible spectrum ranging from blue for activation to green/yellow for deactivation, therefore overlapping with most other optogenetic tools.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, in the case of Cr ChR2, substituting alanine for serine at this position causes a red shift in the absorption spectrum. [32] Nevertheless, the action spectrum of the photocurrents of the HulaCCR C303A mutant showed no significant red shift compared to the WT (Fig. S2c).…”
Section: Resultsmentioning
confidence: 99%